ANALISIS RASIO KEUANGAN UNTUK MEMPREDIKSI PERTUMBUHAN LABA PADA PERUSAHAAN KOSMETIK YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2014-2020 - Nathasya Angellie Tambunan; Richard Friendly Simbolon (Fakultas Ekonomi Universitas Advent Indonesia, 2021)
Cosmetics industry in Indonesia is facing challenges because of the influx of imported cosmetics. In 2016 - 2018, Indonesia’s imported cosmetics sales increased by 30%. This growth has not had much impact on profits earned by the Indonesian cosmetics industry. The objectives of the research are to determine the effect of Current Ratio, Debt to Equity Ratio, Total Assets Turnover Ratio on Profit Growth in Cosmetic Company companies listed on the Indonesia Stock Exchange in the period 2014-2020. This study uses 3 independent variables and 1 dependent variable. The analysis model is a multiple regression analysis with the program spss. The results of testing the hypothesis of this study found that variable Current Ratio (CR), Debt to Equity Ratio (DER), Total Assets Turnover Ratio (TAT) has a negative significance effect on earnings growth.